Effect of chilling hour requirements in breaking buds dormancy in some al-shami mulberry (Morus nigra L.) genotypes - مخول, جرجس; شومان, وفاء; طيبة, خلدون; بارودي, حسام (Latakia University Journal -Biological Sciences Series, 2021)
This study was objected to determine the chill hour requirement in order to break down the bud dormancy of 7 genotypes of al-shami mulberry (Morus nigra L.) cultivated in al-Qunaytirah, Hadar location (Q1, Q4, Q12, Q15, Q17) and Tartous (T4, T6). Studied cuttings left in 2°c in cool chamber for 200, 400, 600, 800, 1000, 1200 and 1400 hours were placed into growth chamber offering temperature, moisture and brightness similar to those available in nature. The results of statistical analysis showed variation between the genotypes, The genotypes of Tartous T4 and T6 needed 14.5, 16.5 days to open buds with 1000 chill hours comparing with al-Qunaytirah genotypes which needed days ranged from 17 to 20.3 days with 1000 chill hour. The number of days to open buds differed with 1400 chill hour so that al-Qunaytirah genotypes were the fast to reach the bud opening with 1400 chill hour. The results of chilling requirement index (CRI) showed significant differences with 800 and 1400 chill hour ranged from 3.86 for T4, 3.52 for T6 and 4.43 For Q15. The significant differences were clear with 1000 chill hour, the highest value of CRI was 4.43 for Q15 and 7.65 for Q12 with 1400 chill hour. To sum it up we can conclude that the more chill hour applied the less Growth degree hour (GDH) is needed to bud opening which was 6480cu for T4 with 800 chill hour and the least GDH value (5400 cu) was with 1400 chill hour for Q15. The cluster configuration between the types was sorted by putting them in two main groups as well with a contrast ratio of 66%. The first group contained Tartous genotypes T4, T6 with a contrast ratio of 48% and the second group contained al-Qunaytirah types with contrast ratio of 36%. The results reveled similarity in Tartous genotypes cuttings behavior with applied chill hours and variance in al-Qunaytirah genotypes cuttings which were similar among themselves too.